Hubungan Antara Pengalaman Ibu Mengalami Kekerasan Dengan Kejadian Stunting Pada Anak - Isra Nur Utari Syachnara Potabuga; Yasni La Harsani; Nur Hafni Hasim (Rena Cipta Mandiri, 2026)
This study aimed to determine the association between maternal exposure to violence and child stunting using data from the Demographic and Health Survey (DHS). The study employed a secondary data analysis design. Data were obtained from the Demographic and Health Survey (DHS) conducted in four countries. The participants were randomly selected married women of reproductive age (15–49 years) who had at least one child under five years of age with complete anthropometric measurements. The exposure variable was maternal experience of violence, including sexual violence, physical violence, or a combination of both. The outcome variable was moderate or severe child stunting, measured using the Height-for-Age Z-score (HAZ) among children aged 6–59 months. Separate Cox proportional regression analyses were performed for each country's dataset to examine the association between maternal exposure to violence and child stunting. The results showed that the prevalence of maternal exposure to violence ranged from 10.17% to 31.00%. The prevalence of child stunting was lowest at 14.04% and highest at 35.86%. The proportion of children with severe stunting was highest at 16.60%, followed by 14.79%. Overall, the findings indicate that maternal exposure to violence is significantly associated with child stunting